Effect of partial substitution of wheat flour (Triticum spp) with vetch flour (Vicia sativa) on the technological and sensory properties of bre - Buitrón, Lucía (2025)
Vicia sativa (common vetch) seeds contain valuable nutrients but are currently unsafe for human consumption. This study assessed the effects of partially substituting (up to 25%) wheat flour (Triticum spp) with vetch flour on the rheological, functional, and sensory properties of dough and bread in order to encourage the development of safe vetch varieties. Vetch flour reduced dough water absorption, though rheological properties remained stable up to 10% substitution. Higher substitution levels decreased bread specific volume (from 3.30 to 1.79 cm3/g), while preserving a satisfactory crumb structure. Sensory tests showed good acceptability of bread appearance and texture up to 10% substitution. Furthermore, correlations were identified between the rheological properties of the dough and the specific volume of the bread.